(untitled) (World Economics and Finance Bulletin, 2022)
The oil sector is one of the primary sectors of the Iraqi economy As it represents the backbone of life and the primary source in generating income, as well as being the critical source in providing foreign currency for the purpose of financing the import process The reason for all this is due to the size of the significant revenues derived from it, which we notice through the linkage of the general budget in Iraq with oil revenues, as it constitutes the most significant part of the general budget Accordingly, any fluctuations in oil prices, especially its decline, will have a detrimental impact on the economy of Iraq; for this reason, the purpose of the research is to demonstrate the effect that shifts in the price of oil have on several aspects of the Iraqi economy , In order to achieve this goal, the standard and analytical aspect has been relied on, It turns out that the Iraqi economy is still dependent on oil to raise the level of the Iraqi economy, Any fluctuations in oil prices, if they were to rise, would be in the interest of the Iraqi economy, and vice versa, Therefore, there must be an urgent necessity to diversify sources of revenue to get rid of oil dependency.